Analisis Ekuitas Merek Terhadap Keputusan Pembelian Produk Skincare Dengan Perilaku Konsumen Sebagai Variabel Intervening (Penelitian komparatif produk skincare Wardah dan Emina di Kabupaten Tulungagung) - Agustine, Vivian farani; Askafi, Eka; Rahmawati, Zulfia (Universitas Islam Kadiri, 2024)
This study aims to determine the Influence of Brand Equity on Purchase Decisions through Consumer Behavior as an Intervening Variable. The study also aims to compare between Wardah Skincare Brand Equity and Emina Skincare Brand Equity whether there is a significant difference between the two skincare brands. This research is a type of quantitative research, with data collection techniques using questionnaires. And the data will be analyzed using the Path analysis method using the SmartPLS3 Application. The population in this study is Wardah Skincare and Emina Skincare Consumers in Tulungagung regency which is infinitely numerous. The sampling technique in this study is using the Accindental Sampling technique. The results of the study showed that Brand Equity had an effect on Consumer Behavior, Consumer Behavior had an influence on Purchase Decisions, Brand Equity had an effect on Purchase Decisions, so all hypotheses were accepted, and the indirect influence hypothesis showed significant value. The comparison between Wardah skincare Brand Equity is more beautiful than that of Emina skincare Brand Equity which can be proven in the results of the Outer model Convergent validity and Validity Discrimination tests.